Is R. Rorty’s Moral Philosophy Possible? Antifoundationalism and Kant’s Criticism - Alijauskaitė, Agnė (Problemos, 2019)
This article aims to answer the main question raised – is Rorty’s moral philosophy possible? To what extent is it possible to treat it as an authentic theory? Rorty’s criticism of Kant and the Kantians, as one of the key points of contemporary moral philosophy, determines the posture in the moral domain and provides a certain place in discourse. The article states that, despite the fact that Rorty’s moral philosophy is not based on a particular theoretical concept, it can be considered as a fragmented whole consisting of several parts, one of which is the agent’s openness to the choice of moral identity. At the same time, we will critically question the position of Rorty himself – while maintaining the suspicion towards the sources of moral knowledge, he maintains an insufficient distance with one of his own sources of moral knowledge, namely historical progress.